PAEDOPHILE AS APARTHEID EVENT: GENEALOGICAL LESSONS FOR WORKING WITH THE APARTHEID ARCHIVE - Bowman, Brett; Hook, Derek (PINS-Psychology in Society, 2025)
The narratives that constitute the beginnings of an apartheid archive do well to illustrate the value of collecting, centralising and analysing everyday accounts of apartheid’s subjects. Developing an archive of narratives that give voice to the quotidian experiences of apartheid is a valuable historical strategy. This approach may be usefully mobilised to offset some of the totalising effects of conventional history writing. Notwithstanding this value, an unreflective turn to narrative as a means to reading the socio-historical and political contours of apartheid, risks reducing critique to a symbolic exercise that centres subjectivity and subject positions as the key analytic targets. Such readings may shift the analysis away from the various levels of materiality and power of which these subject positions are both instruments and effects. In an attempt to demonstrate the way that Foucault’s genealogical maxims may be used to counter the danger of centring the subject in history writing, we present some of the key analytic strategies undertaken in a previous study that produced an effective history of the South African paedophile. In so doing, we argue for a re-scoping of the apartheid archive project to include materials required for undertaking histories of the present. This extension would challenge many of the methodological and political constraints implied by limiting the archive to a corpus of memory narratives.